FIrpic: archetypal blue phosphorescent emitter for electroluminescence. Issue 18 (12th November 2014) - Baranoff, Etienne; Curchod, Basile F. E.
Abstract : FIrpic is the most investigated bis-cyclometallated iridium complex. This Perspective reviews the main experimental and theoretical aspects of FIrpic as well as its use as sky-blue emitter for OLED. Abstract : FIrpic is the most investigated bis-cyclometallated iridium complex in particular in the context of organic light emitting diodes (OLEDs) because of its attractive sky-blue emission, high emission efficiency, and suitable energy levels. In this Perspective we review the synthesis, structural characterisations, and key properties of this emitter. We also survey the theoretical studies and summarise a series of selected monochromatic electroluminescent devices using FIrpic as the emitting dopant. Finally we highlight important shortcomings of FIrpic as an emitter for OLEDs. Despite the large body of work dedicated to this material, it is manifest that the understanding of photophysical and electrochemical processes are only broadly understood mainly because of the different environment in which these properties are measured, i.e., isolated molecules in solvent vs. device.